Pendampingan dan Pelatihan Marketing bagi Pengrajin Gerabah : Marketing - Rasidi, Moh.; Suparman, Muhammad; Abu Amin Fatoni, Novel; Anggun Estu Laksono, Priyo (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Community service aims to improve the marketing and sales skills of pottery products by craftsmen in Alas Kandang Village, Besuk District, Probolinggo Regency. The method used in this research is Participatory Action Research (PAR), which involves the active participation of craftsmen in every stage of planning, implementation, and evaluation of activities. The mentoring was conducted through a series of training activities designed to improve the artisans' understanding of effective marketing strategies. The artisans were also involved in the process of problem identification, solution planning, and change implementation as an effort to improve the competitiveness of their pottery products in the market. The results of the activity showed that through the PAR method, the artisans managed to improve their marketing capabilities, from improving product quality to utilizing social media to expand market reach. By actively participating in the research process, the artisans also developed a sense of ownership of the changes that occurred, thus strengthening the sustainability of their marketing efforts. Through this activity, it makes a positive contribution to local economic development, particularly in increasing the income and welfare of pottery artisans. The practical implication of this PkM activity is that the PAR approach can be an effective model in empowering local communities by involving them directly in the efforts to improve their livelihoods.